Long-term study of the life cycle and growth of Heleobia australis (Caenogastropoda, Cochliopidae) in the Bahía Blanca estuary, Argentina - Carcedo, Maria Cecilia (2012)
The life cycle and growth of the mud-snail Heleobia australis (d?Orbigny, 1835) was studied in the Bahía Blanca estuary (39º S, Argentina) from april 2008 to april 2010. Four year classes were identified. H. australis recruits once a year, during summer. In general, the recruits (< 2.5 mm) represented a small percentage of the total population abundance. The growth rate of H. australis declined with increasing animal size. Growth rate for the population under study shows a marked seasonal pattern: lower rate during winter and higher rate in summer. The obtained information allows us to estimate a life cycle of approximately 30 months (~ 2.5 years) for the population of H. australis in Bahía Blanca estuary. This work constitutes the first long term study of the life cycle of cochliopids. As H. australis appears to be a long-lived species which exhibits variations in life cycle that seem to be influenced by biological and physical variables, future studies should incorporate a number of factors, to better understand variations in life-history traits.